Scientific Significance of the Conference Dedicated to the 105th Anniversary of the Faculty of History: “Current Problems and Prospects for the Development of Armenian Studies’’ - Gabrielyan, Mkhitar (History and Culture, 2025)
The Faculty of History at Yerevan State University, as one of the founding structures of this higher education institution, has a significant role in Armenia’s scientific, educational, and public life. An international conference titled “Modern Issues and Development Prospects of Armenian Studies” was organized within the framework of the 105 th anniversary of the faculty. The conference addressed the interconnectedness of education and science, the necessity of modernizing educational programs, and the growing applied value of historiography. The conference featured approximately one hundred reports from various countries, encompassing fields such as history, archaeology, ethnography, and art history. Particular emphasis was made on the importance of interdisciplinary cooperation for the further development of Armenian Studies. A part of the reports is being published in a special issue of the “History and Culture” journal. Although the conference did not aim to provide comprehensive answers, it served as a valuable platform to highlight sectoral issues and shape the pathways for the development of Armenian Studies and education in the field of history.